Citrus Reset Management - Stephen H. Futch (EDIS)
Replacement of dead and diseased trees in Florida citrus groves has always been an important part of citrus production. Today, tree replacement is more important than ever since overhead and production costs are escalating and a full stand of productive trees is essential to maximize production and profits. In more recent times, Huanglongbing (HLB), or citrus greening, has accelerated tree loss rates as well as the ability for growers to bring young citrus trees into production. This revised 5-page fact sheet discusses a wide range of techniques for providing young tree care. Many of these should prove useful to Florida citrus growers confronted with the problem of managing resets. Written by Stephen H. Futch, and published by the Horticultural Sciences Department, September 2015.